An innovation in teaching and learning of accounting concept using AccRoBa© Game Approach - Mohamad Ridhuan Mat Dangi; Mohd Fairuz Adnan; Mohd Zulfikri Abd. Rashid (Penerbit Universiti Kebangsaan Malaysia, 2017)
The creation of Accounting Royale Balls Game (AccRoBa Game Approach) is to support the learning environment of university students by embarking on the approach of ‘learning through play’ during learning and teaching process. Some lecturer feel that the most common problem on why students face difficulties to understand accounting subject is because they do not mastering the accounting equation especially the topic of revenue and expenses. Therefore, AccRoBa is a game specifically designed to assist students in understanding the element of revenue and expenses in accounting equation and help them to understand better about the journal entry. This study was conducted in a classroom and participated by 250 of non-accounting major students. In this game, the players are required to specify the journal entry and describe whether it is revenue or an expense from the transaction that appears on the given flash card. From the study, most respondents found the game to be beneficial and could be used as a learning tool in the classroom. Majority respondents also agreed that this game can help student to evaluate and classify the assets, liabilities, revenue and expenses easier. Furthermore, this game also encourages peer teaching and learning since it promotes participation and teamwork while students play the game. It is anticipated that the use of this game can alleviate and rejuvenate the learning styles in accounting subject. Since some students have difficulties to understand this subject clearly, hence AccRoBa Game Approach can be the catalyst for the educator to take it as an alternative to mitigate this problem